Analytical study of care quality and moral distress in clinical situations and patient care - Hasanlo Masoumeh; Azarm Arezo; Asadi Parvaneh; Amini Kourosh; Ebrahimi Hossein; Jafarabadi Mohammad Asghari (Sciendo, 2019)
Nursing profession conventionally meets a high standard of ethical behavior and action. One of the ethical challenges in nursing profession is moral distress. Nurses frequently expose to this phenomenon which leads to different consequences such as being bored by delivering patient care that decline care quality and make it challenging to achieve health purposes. This study was conducted to investigate the association between the aspects of moral distress and care quality.